2021
DOI: 10.21660/2021.85.j2184
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Flexural Strength of Lightweight Concrete Beam Using Pumice Stone as of Substitution Partial Coarse Aggregate

Abstract: This research was conducted to analyze the flexural behavior of unreinforced concrete beams produced by substituting coarse aggregate with pumice stones in order to reduce the weight. The specimens used were designed to be 15x15x70 cm in dimension while the coarse aggregate was replaced by the pumice stone at 25%, 50%, 75%, and 100%. Test object without pumice stone (0%) as control beams. The test was conducted at a two-point load with the beam loaded up to the period it failed. The results showed the partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The specimens were crafted with dimensions measuring 15x15x70 cm, and variations were introduced by replacing the coarse aggregate with pumice stone at 25%, 50%, 75%, and 100%. A control beam, devoid of any pumice stone (0%), was also included for comparative testing purposes [2]. Using waste materials as an alternative to coarse aggregate has been shown to affect the environment and the economy positively.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens were crafted with dimensions measuring 15x15x70 cm, and variations were introduced by replacing the coarse aggregate with pumice stone at 25%, 50%, 75%, and 100%. A control beam, devoid of any pumice stone (0%), was also included for comparative testing purposes [2]. Using waste materials as an alternative to coarse aggregate has been shown to affect the environment and the economy positively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that lightweight concrete slabs showed almost the same behavior as the normal weight concrete but because of the reduction in stiffness and ductility they exhibit large deflection and less ductility. Besides, moment capacity is stated to be related to the tensile reinforcement rather than the effect of the weight or strength of the concrete [8][9][10][11][12][13][14][15][16]. In order to increase the stiffness properties of the flexural members, high-strength lightweight concretes were utilized, and good performances were reported [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…This sand is an abundant material in Indonesia, mostly distributed in Jambi, Lampung, West Java, Banten, Jogjakarta, West and East Nusa Tenggara, as well as North Maluku. For the North Maluku region, the aggregate deposits are precisely located on Tidore Island [15].…”
Section: Introductionmentioning
confidence: 99%